2021
DOI: 10.1007/s40195-021-01304-3
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Scattering Studies of Crystallization Kinetics in a Phase-Separated Zr–Cu–Fe–Al Bulk Metallic Glass

Abstract: Thermal stability and the crystallization kinetics of a phase-separated Zr-Cu-Fe-Al bulk metallic glass were investigated using in situ high-energy synchrotron X-ray and neutron diffraction, as well as small-angle synchrotron X-ray scattering. It was revealed that this glass with excellent glass-forming ability possesses a two-step crystallization behavior. The crystalline products and their evolution sequence are more complicated than a homogeneous Zr-Cu-Al glass with average glass-forming ability. The experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…Cubic CuZr 2 , tetragonal CuZr 2 and cubic ZrCu phases are formed during the crystallization. The formation of tetragonal CuZr 2 has been observed in other works in annealed ZrCu [11,54] and in particular Liu et al showed by synchrotron diffraction that during annealing tetragonal CuZr 2 transforms into cubic CuZr 2 in ZrCuAl alloys [55].…”
Section: Thermal Stabilitysupporting
confidence: 52%
“…Cubic CuZr 2 , tetragonal CuZr 2 and cubic ZrCu phases are formed during the crystallization. The formation of tetragonal CuZr 2 has been observed in other works in annealed ZrCu [11,54] and in particular Liu et al showed by synchrotron diffraction that during annealing tetragonal CuZr 2 transforms into cubic CuZr 2 in ZrCuAl alloys [55].…”
Section: Thermal Stabilitysupporting
confidence: 52%
“…The first S(Q) peak shows a lower peak position and a narrower peak width after T C treatment, which indicates that the local order is extended to the medium range and the atomic packing is less dense than the matrix. The structural correlation is enhanced from the short to the medium range (~5-10 Å) during this process, due to the recombination of the local atomic units [22,46,47]. To summarize, the nanoscale thermodynamically-favored metastable amorphous heterogeneous region with an average diameter of 5.4 nm is uniformly distributed in the amorphous alloy matrix.…”
Section: Microstructure and Thermal Analysismentioning
confidence: 97%
“…The first S(Q) peak shows a lower peak position and a narrower peak width after TC treatment, which indicates that the local order is extended to the medium range and the atomic packing is less dense than the matrix. The structural correlation is enhanced from the short to the medium range (~5-10 Å) during this process, due to the recombination of the local atomic units [22,46,47]. To summarize, the nanoscale thermodynamically-favored metastable amorphous heterogeneous region with an Down to the nanoscale, an interference peak occurs in the T C -treated sample whereas it does not exist in the as-cast sample according to the results of SAXS (Figure 1c), which suggests the occurrence of nanoscale heterogeneity different from the amorphous matrix in the T C -treated sample [28,[38][39][40].…”
Section: Microstructure and Thermal Analysismentioning
confidence: 99%
See 1 more Smart Citation